EFFECT OF A METHOD USING CERTAIN PHYSICAL THERAPY DEVICES TO REHABILITATE INFRASPINATUS MUSCLE FOR HANDBALL PLAYERS - Abbas, Amany Alaa (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. Handball players are prone to injuries to the infraspinatus muscle which is caused by repetitive overhead activity and extreme mechanical stress on shoulder joints during play. Hence, the rehabilitation program should be designed in such a way so that shoulder function can be restored and player can resume training safely after infraspinatus injury. Objectives. This research intended to introduce an effective rehabilitation program by using therapeutic devices selected from physical therapy devices and therapeutic exercises for the rehabilitation of handball players with mild tear in infraspinatus muscle.. Method. A single-group experimental study was conducted. Sample size of the study was 10 athletes who were elite handball players in Basra Governorate in season 2023 and had mild tear in infraspinatus muscle. Ten selected physical therapy devices were used for the rehabilitation program along with therapeutic exercises which included movements that targeted enhancing shoulder strength, shoulder flexibility and shoulder range of motion. Study variables included explosive power, speed-strength, spinal flexion–extension and rotation, shoulder joint flexibility which were measured during pre-test and post-test. Data were statistically described using descriptive statistics. Significance was tested at α = 0.05. Results. Results showed a statistically significant difference in explosive power, speed-strength, spinal flexion–extension and rotation, shoulder joint flexibility after performing the rehabilitation program (P < 0.05). Explosive power improved from 4.00 to 6.90, speed-strength from 7.60 to 13.60 repetitions, spinal flexion–extension and rotation from 10.60 to 19.60 repetitions and shoulder flexibility from 46.40° to 110.00°. Conclusion. Sportsmen who had mild tear in infraspinatus muscle experienced improvements in shoulder strength, shoulder flexibility and shoulder range of motion after performing the selected rehabilitation program. This research introduced new rehabilitation protocol which can be implemented in sports injuries and rehabilitation centers to help athletes recover from their injuries quickly and resume training safely.